Upaya Penegakan Hukum Terhadap AI (Artificial Intelligence) Sebagai Subjek Hukum Pidana dalam Perspektif Kriminologi - Beryl Helga Fredella Hibatulloh (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Artificial intelligence, or better known as AI, is experiencing very rapid development in today's technological era. Artificial Intelligence (AI) is an innovation that has changed many aspects of life in the world. The presence of machines with AI capabilities certainly has a disruptive impact on various social structures of society. One of the significant changes with the presence of AI is the legal science course, especially criminal law. The existence of a legal vacuum in the regulation of criminal law enforcement regarding AI or artificial intelligence initiated the author to conduct research related to law enforcement efforts against AI as a criminal law subject. This research aims to find out law enforcement against AI which can be the subject of criminal law. This study uses a type of juridical-normative research with a conceptual approach, a statute approach, and a comparative approach. Legal studies on artificial intelligence as perpetrators of criminal acts are quite minimal because they are not accompanied by regulations that regulate them. Artificial intelligence such as AI cannot perform illegal acts independently, because in its operation, AI requires help from humans. In Indonesia's positive law, artificial intelligence (AI) is not recognized as a legal subject as is a human or legal entity that is juridically recognized as a legal subject. Only legal subjects, both individuals and legal entities, can be held criminally liable. The right conclusion in this article is that the government should prepare regulations on AI as a subject of criminal acts and law enforcement against artificial intelligence. This arrangement is along with the identification of legal subjects, both individuals and legal entities, as well as appropriate laws to carry out law enforcement efforts against AI.